TOTAL QUALITY MANAGEMENT (TQM) PRACTICES AND JOB PERFORMANCE IN PUBLIC SERVICE: A STUDY OF ALVAN IKOKU FEDERAL COLLEGE OF EDUCATION, OWERRI, NIGERIA - Ekemam, Hillary I; Njoku, Benedict N (African Journal of Social and Behavioural Sciences, 2020)
The importance of total quality management practices cannot be overemphasized in the contemporary public service in Nigeria due to ever-increasing demand for improvement in the quality of service rendered by organizations. Most of the public service institutions in Nigeria are characterized by lack of customer focus and poor attitude of management towards relevant staff quality training and development - a situation that has adversely affected the quality of service rendered by the public sector organizations. This study examined the impact of total quality management practices on job performance in public service focusing on Alvan Ikoku Federal College of Education, Owerri. The specific aims of the study are to examine whether total quality management practice affects job performance in the public service; to determine if total quality management customer focus practice can affect job performance in public service, and if total quality training and development practice affects job performance in the public service. Three hypotheses stated in both null and alternative were formulated to guide the study. Descriptive research design was adopted while quantitative primary data was collected from both the academic and nonacademic staff of our focus organization, with the total population of 400 using total quality management practice appraisal questionnaire (TQMPAQ) structured using Likert format. Sequential multiple regression analysis was employed. The goal setting theory and motivation and job satisfaction theory were used to explicate the phenomenon under study. The findings show, amongst others, that there is a significant relationship between total quality management practice and job performance in public service. The study recommends, amongst others, that the management of public sector organizations should show genuine commitment to the effective implementation of total quality management practices in their organizations in order to realize the expected level of job performances.